2021
DOI: 10.1111/bjhp.12556
|View full text |Cite
|
Sign up to set email alerts
|

Social nudges for vaccination: How communicating herd behaviour influences vaccination intentions

Abstract: Objectives. This Registered Report attempted to conceptually replicate the finding that communicating herd immunity increases vaccination intentions (Betsch, et al., 2017, Nat. Hum. Behav., 0056). An additional objective was to explore the roles of descriptive social norms (vaccination behaviour of others) and the herd-immunity threshold (coverage needed to stop disease transmission).Design. An online experiment with a 2 (herd-immunity explanation: present vs. absent) 9 3 (descriptive norm: high vs. low vs. a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…This finding advances Calo et al’s (2021) results that social media messages that appeal to herd immunity significantly increase individuals’ intentions to accept vaccinations. Similarly, Lazić et al (2021) ’s online experiment showed that nudges to inform participants of the social benefits of herd immunity effectively increased vaccination intentions among participants. Expanding these findings obtained from experiments, our review has shown that cultivating the sentiment of a community can be a useful message to promote vaccine adherence among the public.…”
Section: Discussionmentioning
confidence: 99%
“…This finding advances Calo et al’s (2021) results that social media messages that appeal to herd immunity significantly increase individuals’ intentions to accept vaccinations. Similarly, Lazić et al (2021) ’s online experiment showed that nudges to inform participants of the social benefits of herd immunity effectively increased vaccination intentions among participants. Expanding these findings obtained from experiments, our review has shown that cultivating the sentiment of a community can be a useful message to promote vaccine adherence among the public.…”
Section: Discussionmentioning
confidence: 99%
“…As well as economic considerations, there are many social factors underpinning the adoption of a new control mechanism. Descriptive norms (what the majority of people are doing, and thus what is deemed socially acceptable; [ 59 ]) have been found to influence growers’ decision to partake in control [ 60 ]. Relatedly, a grower’s social network and ability to access trusted information has a strong impact on management practices.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that participants were more inclined to participate in a vaccination program that also included an educational component. Education concerning population immunity (e.g., communicating the social benefits of population immunity and designing educational materials that visually demonstrate its effects) is also important in increasing understanding of disease prevention, and hence, willingness to get vaccinated, as shown in previous studies [ 73 ].…”
Section: Discussionmentioning
confidence: 99%